Comparative Analysis of the Heart Tissue Transcriptomes Between Low-altitude Reared and High-altitude Reared Bar-headed Geese (Anser indicus) - Ying LI; Fang WANG; Xiaolong GAO; Lilin ZHU; Wen WANG; Kirill SHARSHOV (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
The bar-headed geese (Anser indicus) are renowned for high-altitude migratory flights and they must fly over the Qinghai-Tibetan Plateau for their annual migration. Through comparing the high-altitude bar-headed geese with the other closely related low-altitude species, many efforts have been made to reveal the unique adaptations at physiological, biochemical, and behavioral levels that help bar-headed geese living and flying in high-altitude conditions. Nonetheless, little is known about the transcriptome level changes of the bar-headed geese adaptation to low-altitude environment. To explore the variations of gene expression that were induced by low-altitude environment in the bar-headed geese, we conducted the first comparative transcriptomic analysis of heart tissues between bar-headed geese reared in high-altitude regions (~3000 m), and the bar-headed geese reared at the low-altitude regions (~30 m) for nearly three years. A total of 76 differentially expressed genes (DEGs) were detected in the low-altitude bar-headed geese compared with the high-altitude bar-headed geese. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that these DEGs were mainly involved in the focal adhesion, extracellular matrix (ECM) - receptor interaction, the mammalian target of rapamycin (mTOR) signaling pathway, wingless-type (Wnt) signaling pathway, and glycosaminoglycan degradation etc. The results will be useful for understanding the divergent adaptation of the bar-headed geese to different altitude environment, and the transcriptome data provides a valuable resource for future functional studies.